Ethnic Personality of Community in the World Heritage Areas of Sukhothai and Angkor Wat - Jindarat, Arunee; Pianchob, Sujrit; Mundee, Boonyung; Wongsawadee, Benjawan (Mediterranean Journal of Social Sciences, 2012)
The research design was mixed methods of quantitative and qualitative approaches. The research design forqualitative research was In-Dept Interview with structural form with 100 peoples comprised 50 Thais, 50 Khmers and quantitativeresearch was survey research with 500 peoples of Thaipuan Ethnic Group who lived in Sukhothai World Heritage Site. Thecontent from qualitative research was analyzed to construct the items for quantitative research. Factor analysis was used fordetermination the component factors of the desirable personality the Thaipuan Ethnic Group in Sukhothai World Heritage Sites.The objectives of this research were to study desirable personality of the Thaipuan Ethnic Group communities at SukhothaiWorld Heritage Sites in Thailand and to analyze component factor of desirable personality of the Thaipuan Ethnic Groupcommunity at Sukhothai World Heritage Sites in Thailand. The finding illustrated that there were 80 items were constructed fromcontent analysis of In-Depth Interview and there were 6 components comprising 1) Honesty, patience and dedication arepersonality of the people in the world heritage sites, 2) Sources meditation practice, moral, and giving would be go along withworld heritage sites, 3) Experience of building and biological knowledge of the ancestors should be inherited from generation togeneration continuously, 4) Creator of the world heritage is the king who practices dharma would be a representative of thepersonality for his people, 5) Traditional craft literacy is educational mechanism for teaching integrity, 6) World heritage reflectssufficient agriculture as remind the patience and kindness.